Theme and Rhythmic Structure in The Poem I Hear America Singing by Walt Whitman - Tazky Aulia Rahmah (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
“I Hear America Singing” by Walt Whitman is a poem of patriotism with diversity in the landscape of America. The aim of this journal is to interpret the motifs and rhythmic forms employed by Whitman in this poem. In the first place, what the paper would like to study are themes in the poem. What is the poem about? The poem is about various types of professions or workers and their occupations in America. The poem ends with a cheerfully inaccurate portrayal of the United States as